The Role of Teaching Grammar in Legal English - Sayfiyeva Komila Kamolidinovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, the educational goal of teaching a foreign language at the level of our country is considered, in the process of teaching a foreign language, to develop the worldview, thinking ability of students, to improve the knowledge acquired in their native language by mastering this language. In this case, knowing the similarities and differences between the mother tongue, Russian and foreign languages will further increase the knowledge level of language learners.